Uji Coba Persiapan Pembelajaran Tatap Muka Masa Normal Baru PAUD “Tunas Bangsa” Semarang - Aji Supriyanto; Jeffry Alfa Rozaq; Agus Budi Santosa; Hersatoto Listiyono (Universitas Mathla'ul Anwar Banten, 2021)
AFTER ONE YEAR OF COVID-19, SEVERAL SCHOOLS HAVE STARTED CONDUCTING TRIALS FOR FACE-TO-FACE LEARNING (PTM) BY IMPLEMENTING HEALTH PROTOCOLS AS A NEW FORM OF NORMAL HABIT. Some parents of